A guide to critiquing research - Part 1 - Quantitative Research - CRONIN, PATRICIA; RYAN, FRANCES; COUGHLAN, MICHAEL (My University, 2007)
When caring for patients, it is essential that nurses are using the current best practice. To determine what this is, nurses must be able to read research critically. But for many qualified and student nurses, the terminology used in research can be difficult to understand, thus making critical reading even more daunting. It is imperative in nursing that care has its foundations in sound research, and it is essential that all nurses have the ability to critically appraise research to identify what is best practice. This article is a step-by-step approach to critiquing quantitative research to help nurses demystify the process and decode the terminology.
PUBLISHED
Keywords: Nursing Education